Unveiling the social and environmental benefits of digital transformation in corporations - Biru Cao; Tianli Wang; Ang Li; Yujie Shang; Jinghao Zhu (PLoS ONE, 2025)
In the context of the “dual-carbon” goal and the digital economy, exploring the impact of digital transformation on enterprises’ social and environmental responsibility is a key issue for achieving sustainable enterprise development and promoting high-quality economic development. This study empirically examines the impact of digital transformation on enterprises’ social and environmental responsibility and its mechanism. We achieved this through using instrumental variables and DID (Differences-in-Differences)models and selecting the data of Chinese A-share listed enterprises from 2008 to 2021. The study concludes that an enterprise’s digital transformation positively contributes to the fulfilment of corporate social responsibility. However, the digital transformation of the enterprise has a dampening effect on the fulfilment of the enterprise’s environmental responsibility. Additionally, this effect holds after a series of robustness tests. Further investigation shows that financial constraints have a positive moderating effect on enterprise digital transformation and corporate social responsibility(CSR) and a negative moderating effect on enterprise environmental responsibility. In addition, we found that the impact of enterprise digital transformation on CSR and environmental responsibility varies by firm type. The above studies provide valuable practical experiences for enterprises to achieve green and low-carbon development, reduce environmental pollution, and realize high-quality economic development as well as insight for enterprises and policy implementers.